2022
DOI: 10.1002/cam4.4748
|View full text |Cite
|
Sign up to set email alerts
|

Tumor regression grade combined with lymph node status in esophageal squamous cell carcinoma after neoadjuvant chemoradiotherapy

Abstract: Introduction:We aimed to elucidate the prognostic value of tumor regression grade (TRG) combined with lymph node status compared with the 8th edition of the ypTNM staging system in patients with advanced esophageal squamous cell cancer (ESCC) after neoadjuvant chemoradiotherapy (nCRT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…In this study, pCR was also not the most important indicator in determining RFS. As for PT-TRG, numerous reports have proved that it has signi cant prognostic implications [21], but some researchers suggest that PT-TRG needs to be combined with pathological TNM staging, which can predict prognosis better in ESCC, this shows that its evaluation function is limited when PT-TRG is associated with LN metastasis [22]. Although in our study not only PT-TRG but also PT responder was not an independent prognostic factor, we could not deny the importance of assessing the responder status of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, pCR was also not the most important indicator in determining RFS. As for PT-TRG, numerous reports have proved that it has signi cant prognostic implications [21], but some researchers suggest that PT-TRG needs to be combined with pathological TNM staging, which can predict prognosis better in ESCC, this shows that its evaluation function is limited when PT-TRG is associated with LN metastasis [22]. Although in our study not only PT-TRG but also PT responder was not an independent prognostic factor, we could not deny the importance of assessing the responder status of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we proposed a novel evaluation approach of combining TRG with ypN status. A few studies reported that the combination of TRG and ypN status had a significant association with survival for esophageal carcinoma 19,23,24 . But no such studies had been conducted for GEJ and GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported that the combination of TRG and ypN status had a significant association with survival for esophageal carcinoma. 19,23,24 But no such studies had been conducted for GEJ and GC patients. In the present study, the combination of TRG and ypN status was recognized to be of great prognostic value for GEJ and GC.…”
Section: Discussionmentioning
confidence: 99%
“…The classi cation methods of prognosis for esophageal squamous cell carcinoma (ESCC) patients who receive nCRT followed by surgery have been explored [5,10]. However, the assessment of TRG using the modi ed Ryan scheme in the CAP Cancer Protocol for Esophageal Carcinoma recommended by the NCCN and CSCO guidelines has not evaluated with the lymph node status for the prognosis of ESCC patients.…”
Section: Introductionmentioning
confidence: 99%